(3GdbGfhLgs
(3ChdgG (B:s
(3hHYO agPG eNJUQ eTJed Ydi RHOI eG jLH ESJMVGQg ai GdWH EfJNHJg ef cJH GdCbOejf GdaUd GdChd ai GdCQcGf hGdCeRLI s
(3BNQgG (B:s
(3GdaUd GdKGdK YTQ ai CMhGd GdWHjN ceG GdMUQe hGdQeGf hGdSeGb hGdJaGM abhJgG eKd bhe YUGQGJgG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefI hGdYTQhfs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs